Dibalik Kecanduan Media Sosial pada Remaja: Pengaruh Stres Akademik dan Kecemasan Sosial dengan Regulasi Emosi sebagai Mediator - Aisyah, Aisyah; Aini, Dewi Khurun; Azaria, Ummi Nabila (Universitas Trunojoyo Madura, 2025)
Academic stress and social anxiety can lead to social media addiction as a form of escape, especially if emotional regulation is unable to manage negative emotions. This study aims to examine the mediating role of emotional regulation in the influence of academic stress and social anxiety on social media addiction in adolescents. This study used a quantitative method, involving 264 students of SMPN X in Semarang City. The sample was determined using a non-probability sampling approach, namely quota sampling. Data analysis used the path analysis method with the help of JASP (Jeffrey's Amazing Statistics Program) version 19.3. The results of the analysis showed that emotional regulation partially mediates the effect of academic stress and social anxiety on social media addiction. This suggests that academic stress and social anxiety can increase the risk of social media addiction, especially if accompanied by low emotional regulation abilities. Thus, schools have a strategic role in improving students' emotional regulation, especially in managing academic stress and social anxiety through psychoeducational programs and counseling as a preventive measure to prevent or reduce the level of social media addiction among students.